Telaah Hukum tentang Pembatalan Peraturan Daerah (PERDA) oleh Pemerintah Pasca Putusan Mahkamah Konstitusi Nomor : 56/PUU-XIV/2016 - Fathorrahman Fathorrahman (JURNAL RECHTENS, 2017)
After the revocation of several paragraphs in Article 251 of Law Number 23 Year 2014 on Regional Government by the Constitutional Court, the Central Government no longer has the authority in an effort to overrule the Regional Regulations of the Regency / City. The cancellation of the perceived regional regulation must be through the instrument of the judiciary, in which case its cancellation must be through judicial review to the Supreme Court. So the principle of executive review is no longer allowed cancellation of a Perda and Perkada by the government that is above it.